Chronological in vivo imaging reveals endothelial inflammation prior to neutrophils accumulation and lipid deposition in HCD-fed zebrafish. (November 2019) - Luo, Hui; Li, Qi-qi; Wu, Ni; Shen, Yu-ge; Liao, Wei-ting; Yang, Yun; Dong, E.; Zhang, Gui-min; Liu, Bin-rui; Yue, Xiao-zhu; Tang, Xiao-qiang; Yang, Han-shuo
Abstract: Background and aims: Hyperlipidemia-induced atherosclerosis is the major cause of heart attack and stroke in humans. However, pathological details and molecular mechanisms underlying early atherogenesis remain incompletely characterized. This study explored the early events of atherogenesis in a hypercholesterolemic zebrafish model in vivo . Methods: We used transparent transgenic zebrafish larvae Tg(lysc:EGFP), Tg(mpx:EGFP), Tg(mpeg1:EGFP), Tg(flk1:EGFP) or Tg(lysc:EGFP/flk1:mCherry), together with fluorescently labeled control and high cholesterol diets (HCD), to dynamically investigate the early development of atherosclerosis with confocal in vivo . Endothelial cells with green fluorescence were sorted by fluorescence-activated cell sorting (FACS) to detect gene expression. Moreover, we treated hypercholesterolemic zebrafish model in vivo or human umbilical vein endothelial cells (HUVEC) in vitro with rosiglitazone, an agonist of peroxisome proliferator-activated receptor γ ( PPARγ ). Results: We found that HCD-induced endothelial inflammation was an earlier pathological alteration than myeloid cells/neutrophils accumulation and lipid deposition in zebrafish vascular vessels of HCD-fed zebrafish. Endothelial inflammation was characterized by down-regulation of anti-inflammatory PPARγ and upregulation of pro-inflammatory tumor necrosis factor α ( TNF-α ) and interleukin-1β ( IL-1β ). Pharmacological treatment with rosiglitazone reversed the decrease in the expression of PPARγ and decreased expression of TNF-α and IL-1β in HCD-fed zebrafish. Moreover, rosiglitazone ameliorated myeloid cells accumulation and lipid deposition in HCD-fed zebrafish in vivo . Conclusions: Hyperlipidemia-induced endothelial inflammation happens earlier than myeloid cell neutrophils accumulation in vascular vessels, and neutrophils accumulation is prior to lipid deposition during the initial stage of atherosclerosis. Early alleviation of inflammation induced by HCD would have a prophylactic effect for the initial development of atherosclerosis. Graphical abstract: Image 1 Highlights: Endothelial inflammation is prior to neutrophils accumulation and lipid deposition during the early atherogenesis. Endothelial inflammation is characterized by the down-regulation of PPARγ and the up-regulation of TNF-α and IL-1β . PPARγ agonist rosiglitazone inhibits HCD-induced up-regulation of TNF-α and IL-1β by reversing PPARγ expression . Rosiglitazone ameliorated myeloid cells/neutrophils accumulation and lipid deposition in HCD-fed zebrafish .